Assessing metacommunity processes through signatures in spatiotemporal turnover of community composition. (21st June 2020) - Jabot, Franck; Laroche, Fabien; Massol, François; Arthaud, Florent; Crabot, Julie; Dubart, Maxime; Blanchet, Simon; Munoz, François; David, Patrice; Datry, Thibault
Abstract: Although metacommunity ecology has been a major field of research in the last decades, with both conceptual and empirical outputs, the analysis of the temporal dynamics of metacommunities has only emerged recently and consists mostly of repeated static analyses. Here we propose a novel analytical framework to assess metacommunity processes using path analyses of spatial and temporal diversity turnovers. We detail the principles and practical aspects of this framework and apply it to simulated datasets to illustrate its ability to decipher the respective contributions of entangled drivers of metacommunity dynamics. We then apply it to four empirical datasets. Empirical results support the view that metacommunity dynamics may be generally shaped by multiple ecological processes acting in concert, with environmental filtering being variable across both space and time. These results reinforce our call to go beyond static analyses of metacommunities that are blind to the temporal part of environmental variability. Abstract : We propose a novel analysis framework to assess metacommunity processes using path analyses of spatial and temporal diversity turnovers. We apply this framework to simulated datasets and to four real datasets. Empirical results support the view that metacommunity dynamics may be generally shaped by multiple ecological processes acting in concert, with environmental filtering being variable across both space and time.